PEMBERIAN LIMBAH CAIR PABRIK KELAPA SAWIT TERHADAP PERTUMBUHAN BIBIT KARET (Hevea brasiliensis) STUM MINI - Hot Aryanto Sitompul; Husna Yetti; Arnis En Yulia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aimed to determine the effect of Palm Oil Mill Effluent (POME) and get the best treatment waste palm oil mill in the growing seed rubber stum mini. This research was conducted in experimental garden of Agriculture Riau University at Bina Widya of subdistrict Simpang Baru, district Tampan, Pekanbaru from April to July 2014. This research was conducted using a Completely Randomized Design (CRD) with 6 treatments and 4 replications thus obtained 24 experimental units, each unit consist of 2 plants. The treatments are L0: not LCPKS, L1: 1,6 L LCPKS, L2: 2,4 L LCPKS, L3: 3,2 L LCPKS, L4: 4,0 L LCPKS and L5: 4,8 L LCPKS. Data were analyzed using ANOVA and followed by further test DNMRT at 5% level. The results of research indicate that of effect of palm oil mill effluent real effect on the parameter of the root crown ratio, but had nod significant effect on parameters of height seed, number of leaves, tuber diameter, seed dry weight and rubber seeds roots volume. Effect of 2,4 L LCPKS indicate the best growth in all of parameters but effect of 1,6 L LCPKS in volume of rubber seedling roots. Keyword : palm oil mill effluent (POME) and rubber seed stum mini